Les forets de montagne de la Nouvelle-Caledonie: Montane forests in New Calidonia - Nasi, Robert; Jaffre, T.; Sarrailh, J.M. (2002)
Higher local temperature gradients near isolated mountains (inselbergs) result in continuous cloud cover at below normal elevations, creating the right conditions for the development of montane forests in New Caledonia at altitudes below 1600 m. These forests are especially important for biodiversity and to improve our understanding of the phytogeography and phylogeny of groups such as conifers or genera such us Metrosideros (Myrtaceae) and Cunonia (Cunoniaceae). They provide vital refuge areas for endangered fauna and play a significant role in water regulation. These forests are relatively well protected, with few threats from logging though slightly more from mining activities. The main threat seems to be the global warming phenomenon, which could cause the disappearance of the very specific ecological conditions that are vital to their survival.